An integrated buffer management strategy for the TDD mode in IEEE 802.16 BWA networks. (1st January 2012) - Liang, Chia-Chuan; Wu, Jung-Shyr
Considering IEEE 802.16 networks having different types of service flows, in this paper, we propose a rearranging scheme of a two-tier hierarchy for the TDD mode in IEEE 802.16 broadband wireless access networks to dynamically adapt to the traffic burstiness according to the change of instant buffers on buffer management. We demonstrate the performance improvement of the rearranging scheme in terms of accumulated throughput and fairness in the finite buffer case compared with the fixed rule by simulations. The simulation results show that the proposed scheme in the case of finite buffer depth not only can provide much better fairness and achieve higher accumulated throughput but also is less buffer-consuming than that without rearranging, meaning that the hardware cost can be reduced by employing the proposed scheme.